Design of a Mobile Augmented Reality Platform with Game-Based Learning Purposes - Costa, Maria Cristina (2021)
Augmented reality (AR) is an emergent technology that overlays virtual objects into the real environment. Lately, AR is gaining prominence in education because of its increasing affordability through computers or mobile technologies. In addition, research sustaining the benefits of AR to promote student’s engagement to learn is increasing every day. However, the literature identifies lack of studies about the use of AR in education, namely, studies focused on the development of AR games designed over specific learning objectives (game-based learning). This paper presents a mobile augmented reality platform with learning purposes. The platform includes a mobile application that consists of a location-based game targeted to promote learning about the universe. Furthermore, it includes a back-office that allows teachers to introduce information about celestial bodies and also develop a set of multiple-choice questions to assess student’s learning about the subject matters they teach. The mobile application provides the users with physical movement and social interaction in the real world, while playing the game and for this reason it is included in the pervasive games’ paradigm. Besides engaging the students to play the game, we argue that this platform may be used as a resource to be implemented in informal and formal learning environments.